State Production and Market at Ebla – Animal and Wool Values - Alfonso Archi (Asia Anteriore Antica)
The kingdom of Ebla covered an area extending around 200 km from north to south and from east to west; that is, from the modern Syrian-Turkish border down to the oasis of Ḥama in the south, and from the Amuq plain, where the delta of the Orontes River flows into the Mediterranean Sea, up to Emar, its allied city, whose territory reached the Euphrates. The Central Administration – the Palace – had at its disposal the revenues from its own administrative organization, with its workshops, as well as from the “village communities”, represented by a large number of “Elders”. Notwithstanding that, Ebla’s envoys also acquire several types of goods, such as mules, cattle and sheep, garments and wool, from the markets of the cities in its own kingdom, and in other city-states, primarily from its archival, Mari. Luxury goods, on the other hand, were mostly acquired on the basis of ceremonial gifts from court to court. Long-distance-trade, however, was not relevant in the formation of the Syrian regional states. Goods (including the tributary deliveries its officials owed the Palace) were given also values in silver, and small goods, such as aromatic essences, were valued in wool. The average value of a head of cattle was around 25 shekels of silver, while a sheep was worth between 1 and 1½ shekels. It is not possible to establish the exact value of the weight used for wool. These prices are in any case much lower compared to those used in Mesopotamia during the Ur III period.